2020
DOI: 10.1007/s12282-020-01116-w
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of the anatomic stage and pathological prognostic stage according to the AJCC 8th edition for the prognosis in Japanese breast cancer patients: data from a single institution

Abstract: Background The TNM system, which reflects the anatomical extent of disease, was used for stage definition. In the recently published AJCC 8th edition, the new staging system of the clinical and pathological prognostic stage, which incorporates biological factors, is introduced. Patients and methods A total of 2622 patients with primary breast cancer at stage I–III were included in this study. The anatomic stage (aStage) and the pathological prognostic stage (ppStage) for each case were determined according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The head mask and baseplate in the thermoplastic fixation can effectively fix the patients to make them feel comfortable and safe during treatment, and the groove and fixing lugs in the baseplate not only facilitate the fixation of headrest but also increase the comfort level [21][22][23]. Besides, Tokunaga et al [24] have pointed out that thermoplastic fixation has remarkably smaller set-up errors compared with the breast bracket and can effectively enhance radiotherapy effect and benefit the patients' prognoses. Tables 3, 4, and 5 in this paper present the analysis results of set-up errors of the breast bracket and thermoplastic fixation.…”
Section: Discussionmentioning
confidence: 99%
“…The head mask and baseplate in the thermoplastic fixation can effectively fix the patients to make them feel comfortable and safe during treatment, and the groove and fixing lugs in the baseplate not only facilitate the fixation of headrest but also increase the comfort level [21][22][23]. Besides, Tokunaga et al [24] have pointed out that thermoplastic fixation has remarkably smaller set-up errors compared with the breast bracket and can effectively enhance radiotherapy effect and benefit the patients' prognoses. Tables 3, 4, and 5 in this paper present the analysis results of set-up errors of the breast bracket and thermoplastic fixation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the prognostic staging assesses the histological grade of the tumor and the presence or absence of hormone receptors (ER and PR) and HER2. Currently, the Oncotype Dx ® genomic test can also be evaluated 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies have shown greater accuracy when evaluating the pathological-prognostic staging to define patient management 32 . Yet, as the objective of this study was only to investigate whether molecular subtypes influenced the disease staging, no adjuvant therapy was analyzed; thus, no further statements on the subject are pertinent.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicopathologicalfeatures, such as age, clinical stage, and tumor classi cation are major predictors of survival outcomes in patients with BC (14). Recent researches have shown that RBP is closely related to the occurrence and development of various cancers and plays a critical role in tumor invasion, migration, and metastasis (15).…”
Section: Discussionmentioning
confidence: 99%